Diels-Alder Reactions of Pyrimidine o-Quinodimethanes: Stereochemistry and Applications to the Synthesis of Tetrahydro- and Quinazoline Derivatives - Herrera, Antonio; Martinez-Alvarez, Roberto; Chioua, Mourad; Chioua, Rachid; Almy, John; Sanchez, Angel (Letters in Organic Chemistry, 2006)
The Diels-Alder reactions of the ortho-quinodimethane (o-QDM) thermally generated from 2,4- diphenylciclobutapyrimidine with the dienophiles diethyl maleate, diethyl fumarate and dimethyl acetylenedicarboxylate have been investigated. The reaction afforded 5,6,7,8-tetrahydroquinazoline and quinazoline derivatives. While diethyl maleate formed a mixture of cis- and trans-adducts, diethyl fumarate gave only the trans-adduct. The reaction with methyl acetylenedicarboxylate formed a mixture of 5,8- dihydroquinazoline and quinazoline derivatives.
Keywords: quinazolines